Strategi Pemasaran Online Terhadap Peningkatan Laba UMKM di Desa Sukamantri - Rismawati Rismawati; Amelia Sri Rizki; Tabina Farrah Anindya; Assyfa Putri Amalia; Winda Fara Setiani (Journal Economic Excellence Ibnu Sina, 2025)
E-commerce has become one of the significant innovations in the world of trade, offering various benefits for consumers and businesses, especially Micro, Small and Medium Enterprises (MSMEs). This research aims to explore the benefits and limitations of e-commerce for both parties. For consumers, e-commerce provides the flexibility to shop 24 hours a day without location restrictions, reduces the need for travel, and provides quick access to product information. Consumers can also enjoy a wider selection of products, competitive prices, and services such as virtual auctions and fast delivery. These advantages open up opportunities for consumers from various economic circles to obtain the desired products more easily. On the other hand, entrepreneurs, especially MSMEs, benefit from operational cost efficiencies, the ability to reach global markets, and the potential for specialized business success. However, there are some limitations, such as lack of security, risk of fraud, and imperfections in the visualization of products offered online. Entrepreneurs also face challenges in managing websites, intense price competition, and legal uncertainty regarding online transactions. Nevertheless, the use of e-commerce continues to grow, supported by the increasing number of internet users and technological advances. The results of this study show that although e-commerce has constraints, the advantages it offers, in terms of efficiency, market reach, and ease of access, far outweigh its limitations. Therefore, optimal utilization of e-commerce can drive economic growth, improve the competitiveness of MSMEs, and expand consumer access to products and services in the digital era.